Field evaluation of Indian gooseberry (Emblica officinalis) accessions for yield, fruit quality and antioxidant potential - PANDEY, D; PANDEY, G; PANDEY, AVNISH; DUBE, APARNA (The Indian Journal of Agricultural Sciences, 2016)
Ten diverse promising genotypes of Indian gooseberry (Emblica officinalis Gaertn.) along with two commercial varieties, viz, NA-6 and NA-7 were evaluated during the year 2013 and 2014 for commercial potential based on tree growth and physico-chemical characteristics. Maximum plant height was recorded in genotype CISH A-19 (7.11m) and minimum in NA-6 (4.13m). Plant spread in East-West and North-South directions varied from 3.01-5.13m and 2.91-4.89m respectively, while plant girth was recorded maximum in CISH A-19 (63.88 cm). Pulp weight varied from (22.91-33.92g), recorded highest in genotype CISH A-31 (33.92g) while lowest weight was found in CISH A-17 (22.91g). Large variations in fruit shape, viz. oval round, flattened round, round, conical, flattened oblong and flattened oval was noticed amongst the genotypes. Similarly, fruit colour at maturity among different genotypes recorded as green, light green and pinkish. Fruit weight varied from 24.37 to 35.41g among the different genotypes being highest in genotype CISH A-19 (35.41g) which is significantly higher than the standard check varieties NA-6 (28.49g) and NA-7 (30.30g). No significant difference was recorded amongst the studied material with respect to standard check for fruit length and fruit diameter. Significantly higher percentage of pulp was recorded in CISH A-31 (95.60%) compared to check NA-6 (94.77%) and NA-7 (95.01%). Stone size with respect to length ranged from 1.02-1.15cm being highest in CISH-A-15 (1.15 cm) while stone width was recorded maximum in CISH A-1 and CISH A-2 (1.06cm). Stone weight varied from 1.46-1.57g being maximum recorded in CISH A-19 (1.57g) and minimum in CISH A-17 (1.46g). Considerable variation in fruit yield (26.14 to 52.50 kg/tree) from 6 years old trees were observed. Highest fruit yield was recorded in genotype CISH A-31 (52.50 kg/tree) followed by CISH A-3 (48.11 kg/tree) which is highly significant compared to standard check NA-6 (32.90 kg/tree) and NA-7 (35.76kg/tree). The chemical parameters, viz. vitamin-C content ranged from 309.66-473.13 mg/100g, TSS (9.3-10.6 0B), acidity (1.49-2.88%), total sugar content (5.66-6.89%), polyphenol content (0.633-1.427 mg/100g) and FRAP activity (102.01-235.76 mg/100g FeSO4) among different accessions evaluated. Conclusively, based on yield, associated physico-chemical traits and antioxidant value, genotype CISH A-31 found most promising and can be recommended for future commercialization.